Pengaruh Sistem Samsat Drive Thru, Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, Dan Sanksi Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Shinta Mustika Hutabarat; Juliana Nasution (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This study was designed to examine the effect of driving through the Samsat system, taxpayer knowledge, taxpayer awareness, and motor vehicle tax sanctions on motor vehicle taxpayer compliance with the PKB of the Medan City Tax and Correctional Authority. The type of data used in this study is raw data collected through a questionnaire to answer the researcher's questions. To test this hypothesis, the researcher used multiple linear regression model to find the relationship between the variables studied. The results showed that the drive-thru system, taxpayer knowledge, taxpayer awareness, and motor vehicle tax sanctions had no significant effect on motor vehicle tax compliance.